Avaliação do xenoenxerto de pele de tilápia na sensibilidade dolorosa em pacientes com queimaduras de segundo grau superficial e da validade concorrente de um novo instrumento de mensuração da dor em queimados - Diógenes, Ana Kely de Loyola (2021)
The use of Tilapia skin as a biological dressing is a low-cost option and offers the requirements for occlusive dressing. In previous studies it obtained a good result in the tensiometric and skin sensitivity tests in the pre-clinical and clinical phase II phases in which the Tilapia skin showed better results than the conventional treatment, mainly in painful symptoms. The pain caused by burns is one of the main characteristics present throughout the treatment until the restructuring of the injured skin. The search for the comfort of burned patients and a more specific method for pain assessment is necessary for the perspective of a better care and treatment plan. The aim of this study was to characterize and evaluate the concurrent validity of a new method of measuring pain in burn patients and to compare the effect of Tilapia skin with silver Sulfadiazine in patients with superficial second degree burn by assessing painful sensitivity. This work was divided into two subprojects, namely: Part I: Concurrent validity of a new method for assessing pain in burned patients the Von Frey Eletrônico (vFE). Part II: Tilapia skin as a dressing in patients with superficial second degree burns: evaluation of painful sensitivity. This was a prospective, open, monocentric, randomized study with active control. The study lasted 19 months in the outpatient clinic of the Burn Center of the Instituto Doutor José Frota (IJF). It counted on the collaboration of 116 volunteers, who were randomly divided into group F1, treated with tilapia skin and group F2, treated with 1% silver sulfadiazine ointment. The results of part I showed that there is a very good correlation between vFE and Visual Analogue Scale (VAS) in the overall pain intensity. The clinical and demographic characteristics do not influence the assessment of pain by the vFE test. In addition, there was a positive correlation between pain, dipyrone consumption and anxiety only when the assessment was made by the vFE test, which is more sensitive than the EVA and thus it is concluded that the vFE can be used as an instrument for assessing the pain in burn patients. The results of Part II, pain assessment in burned patients treated with Tilapia Skin, show that the treatment of burns with Tilapia Skin showed a lower overall pain index than silver sulfadiazine, happening earlier, from visit 3, lasting until the end of treatment. There was no difference in the assessment of anxiety related to painful procedures (BSPAS) comparing the two groups. Additionally, the treatment of burns with Tilapia Skin showed a lower consumption of dipyrone, less days of total re-epithelialization and a lower number of dressings when compared to patients treated with silver sulfadiazine. We can conclude that Tilapia skin xenograft is more effective in reducing painful sensitivity in patients with superficial 2nd degree burns when compared to silver sulfadiazine.